2017
DOI: 10.1155/2017/6756793
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a Nanoemulsion with Carapa guianensis Aublet (Meliaceae) Oil by a Low‐Energy/Solvent‐Free Method and Evaluation of Its Preliminary Residual Larvicidal Activity

Abstract: Andiroba (Carapa guianensis) seeds are the source of an oil with a wide range of biological activities and ethnopharmacological uses. However, few studies have devoted attention to innovative formulations, including nanoemulsions. The present study aimed to obtain a colloidal system with the andiroba oil using a low-energy and organic-solvent-free method. Moreover, the preliminary residual larvicidal activity of the nanoemulsion against Aedes aegypti was evaluated. Oleic and palmitic acids were the major fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 27 publications
2
7
0
1
Order By: Relevance
“…For example, a nanoemulsion against Aedes aegypti has been developed separately based on andiroba and copaiba oils with required hydrophilic-lipophilic balance (rHLB) values of 11.2 and 14.8. The nanoemulsions were found to be stable when the HLB value of surfactants was near to the rHLB oil in the system [17,18]. This study has strongly confirmed that when the HLB value of surfactants is similar to the rHLB of the oil used in the system, the most stable nanoemulsion was produced.…”
Section: Surfactant As An Emulsifier In Nanoemulsionsupporting
confidence: 69%
See 1 more Smart Citation
“…For example, a nanoemulsion against Aedes aegypti has been developed separately based on andiroba and copaiba oils with required hydrophilic-lipophilic balance (rHLB) values of 11.2 and 14.8. The nanoemulsions were found to be stable when the HLB value of surfactants was near to the rHLB oil in the system [17,18]. This study has strongly confirmed that when the HLB value of surfactants is similar to the rHLB of the oil used in the system, the most stable nanoemulsion was produced.…”
Section: Surfactant As An Emulsifier In Nanoemulsionsupporting
confidence: 69%
“…The non-heating process also was suggested where essential oil has been used in the nanoemulsion formulation. Recently, this method has been used to develop nanoemulsions in controlling Aedes aegypti mortality [18,70].…”
Section: Low-energy Methodsmentioning
confidence: 99%
“…Kassir and coworkers [ 51 ] observed a 20% LC 50 reduction from 24 to 48 h (from 53.8 to 32.52 μg mL −1 ) after incubation of pure limonene with Culex quinquefasciatus . The enhancement of activity may be associated to gradative release of the larvicidal compounds from nanostructure systems as nanoemulsions [ 52 ]. Further studies aiming to correlate the release of compounds with mortality as function of time should be performed to better understanding of the phenomena involved in the larvicidal action of nanoemulsions, including those based on B. reticularia .…”
Section: Discussionmentioning
confidence: 99%
“…3 3.6, 152.8 6.8, 129.5 3.0, 119. 4 3.1, 121.4 2.7, 114.5 2.9, and 123.0 3.5 at 3, 100, 30, 3, 30, 30, and 10 μM, respectively, without causing cytotoxicity. In particular, 1 and 4 showed relatively potent activities, which were comparable to that of our previously reported perennisoside I.…”
Section: Resultsmentioning
confidence: 96%
“…6 2.5 and 7-deacetoxy-7α-hydroxygedunin 4, 119. 4 3.1 ; 2 andirolide H 5, 107.8 3.3 at 3 μM ; iii compounds with an α,β-epoxy-g-lactone moiety in the D-ring exhibited higher activity than that with an α,β-unsaturated cyclopentanone moiety 1 17β-hydroxyazadiradione 8, 97. 5 4.3 at 3 μM .…”
Section: Effect Of the Principal Limonoids 1-10 On Collagenmentioning
confidence: 98%